Autonomous rehabilitation at stroke patients home for balance and gait: safety, usability and compliance of a virtual reality system - Help, Jeremia P.; Ferrer, Begoña; Mainetti, Renato; Steblin, Alexander; Hertler, Benjamin; Moreno-Conde, Alberto; Dueñas, Álvaro; Pájaro, Marta; Parra-Calderón, Carlos L.; Vargiu, Eloísa; Zarco, María J.; Barrera, María; et al. (Edizioni Minerva Medica, 2017)
Background: New technologies, such as telerehabilitation and gaming devices offer the possibility for patients to train at home. This opens the challenge of safety for the patient as he/she is called to exercise neither with a therapist on the patients' side nor with a therapist linked remotely to supervise the sessions. Aim: To study the safety, usability and patient acceptance of an autonomous telerehabilitation system for balance and gait (the REWIRE platform) in the patients home. Design: Cohort study. Setting: Community, in the stroke patients' home. Population: Fifteen participants with first-ever stroke, with a mild to moderate residual deficit of the lower extremities. Methods: Autonomous rehabilitation based on virtual rehabilitation was provided at the participants' home for twelve weeks. The primary outcome was compliance (the ratio between days of actual and scheduled training), analyzed with the two-tailed Wilcoxon Mann-Whitney test. Furthermore safety is defined by adverse events. The secondary endpoint was the acceptance of the system measured with the Technology Acceptance Model (TAM). Additionally, the cumulative duration of weekly training was analyzed. Results: During the study there were no adverse events related to the therapy. Patients performed on average 71% (range 39 to 92%) of the scheduled sessions. The TAM Questionnaire showed excellent values for stroke patients after the training. The average training duration per week was 99±53min. Conclusions: Autonomous telerehabilitation for balance and gait training with the REWIRE-system is safe, feasible and can help to intensive rehabilitative therapy at home. Clinical rehabilitation impact: Telerehabilitation enables safe training in home environment and supports of the standard rehabilitation therapy.
Keywords: Enfermos - Rehabilitación - Innovaciones tecnológicas; Telerehabilitación; Innovación tecnológica; Aceptación